Equilibrium outcomes of Lindahl-endowment pretension games - Sertel, M.R.; Sanver, M.R. (Elsevier, 1999)
This paper considers an economy with a single private and a single public good, where the preferences of the agents are common knowledge but initial endowments of the population are unknown. The public good is produced by the initial endowments of the agents. We ask what happens if a 'Lindahl government' (endowment pretension mechanism) is instituted, which directly asks the agents to reveal their initial endowments. Under mild assumptions, we characterize the allocations which would be obtained by this method at undominated Cournot (Nash) equilibria, and we determine when these allocations coincide with the allocations at a voluntary contributions equilibrium.
Keywords: Games Of Pretension; H41; Lindahl Solution; Manipulation Via Hiding Of Endowments; Undominated Nash Equilibrium; Voluntary Contributions Equilibrium